1983
DOI: 10.1051/lait:1983629-63019
|View full text |Cite
|
Sign up to set email alerts
|

Migration du calcium et des phosphates inorganiques dans les fromages à pâte molle de type Camembert au cours de l'affinage

Abstract: Au cours de l'affinage des fromages à pâte molle de type camembert, le calcium et les phosphates migrent de l'intérieur vers la croûte où les teneurs en ces deux éléments peuvent respectivement dépasser 17 et 9 g/kg. La migration de ces minéraux coïncide avec le développement du Penicillium caseicolum mais se trouve en réalité sous la dépendance du pH; en effet, c'est par suite du développement de Penicillium caseicolum que se crée un gradient de pH dans le fromage. Des fromages qui ont reçu une pulvérisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
3
3

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 2 publications
4
19
3
3
Order By: Relevance
“…The alkalinization of the rind was observed from day 0 to day 14 ( Fig. 1) and corresponded to what is generally reported for Camembert-type cheese (11,19,25). The initial rind pH of 4.54 increased to 8.10 at day 14 and remained stable until the end of ripening at day 31.…”
Section: Resultssupporting
confidence: 84%
“…The alkalinization of the rind was observed from day 0 to day 14 ( Fig. 1) and corresponded to what is generally reported for Camembert-type cheese (11,19,25). The initial rind pH of 4.54 increased to 8.10 at day 14 and remained stable until the end of ripening at day 31.…”
Section: Resultssupporting
confidence: 84%
“…This suggested that proteolysis was more responsible for the changes in texture and meltability of processed cheeses than the Ca equilibrium. The Ca content of processed cheeses was dependent on mineral phosphorus content (Graet and others 1983). During the manufacture of processed cheeses, the added emulsifying salts, mainly citrates and phosphates, might have destroyed the Ca equilibrium in the matrix and caused the formation of a new balance between casein‐bound Ca and the soluble Ca.…”
Section: Resultsmentioning
confidence: 99%
“…The Gouda‐type cheese samples were taken periodically during ripening and frozen at −20 °C until analysis. The ash content of milk and cheese samples was determined according to Le Graët et al. (1983).…”
Section: Methodsmentioning
confidence: 99%